QTL association mapping - Weir, Bruce (Henry Stewart Talks, 2007)
QTLs affect continuous traits, Generally mapped from pedigree or family data, Genome-wide association studies extended to QTLs, Alternative models for genetic values, Regress trait values on genetic markers, Power of regression tests, Case-control tests when QTL governs probability of affection, Case-only Hardy-Weinberg tests